Tenure insecurity and incremental housing development in the peri-urban interface of Ibadan, Nigeria - Alabi, Moruf (2021)
The increasing urbanization being experienced in countries of Africa exacerbates current housing needs and tenure insecurity. In Ibadan, Nigeria, the urban populace finds it easier to access land in the informal land market because of the strictness of the formal land market. This results in incremental housing development. Based on the self-help theory, the study examined the contribution of tenure insecurity to the development of incremental housing in peri-urban Ibadan. A cross-sectional research design and mixed methods were employed in the study. 248 household heads were selected from 6 LGAs of Ibadan and administered with a structured questionnaire. Ethical protocols were followed and informed consent was obtained. The study revealed that the majority of the incremental developers were illiterates. Factors that accounted for the incremental development included fear of eviction, high housing rent, and lack of funds. The study recommended enhancing access to secure land titles as it has multiplier-effects on housing.